Modelling the blast environment and relating this to clinical injury: experience from the 7/7 inquest. Issue 2 (19th February 2014) - Hepper, Alan E; Pope, D J; Bishop, M; Kirkman, E; Sedman, A; Russell, R; Mahoney, P F; Clasper, J
Abstract : This paper addresses the computational modelling of a series of specific blast-related incidents and the relationships of clinical and engineering interpretations. The Royal Centre for Defence Medicine and the Defence Science and Technology Laboratory were tasked in 2010 by the UK Ministry of Defence to assist the Coroner's inquests into the 7 July 2005 London bombings. A three phase approach was taken. The first phase included an engineering expert in blast effects on structures reviewing photographs of the damaged carriages and bus to give a view on the likely physical effects on people close to the explosions. The second phase was a clinical review of the evidence by military clinicians to assess blast injury in the casualties. The third phase was to model the blast environment by structural dynamics experts to assess likely blast loading on victims to evaluate the potential blast loading on individuals. This loading information was then assessed by physiology experts. Once all teams (engineering, clinical and modelling/physiological) had separately arrived at their conclusions, the information streams were integrated to arrive at a consensus. The aim of this paper is to describe the methodology used as a potential model for others to consider if faced with a similar investigation, and to show the benefit of the transition of military knowledge to a civilian environment.